2018
DOI: 10.1111/cid.12585
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and augmentation of molar extraction sites affected by severe bone defect due to advanced periodontitis: A prospective clinical trial

Abstract: Ridge preservation at periodontally compromised molar extraction sites might compensate for ridge width and buccal bone resorption that occurs with natural healing alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 45 publications
6
71
0
Order By: Relevance
“…Several studies, including the present study, have demonstrated the effect of ARP specifically in molar areas (Cha et al, ; Lombardi et al, ; Walker et al, ; Zhao, Xu, Hu, & Chung, ). All of these studies favoured ARP over natural healing in terms of maintaining ridge dimension, but high heterogeneity among studies should be considered (Cha et al, ; Lombardi et al, ; Walker et al, ; Zhao et al, ), such as jaw and socket morphology, biomaterial, surgical technique (flap reflection and primary flap closure), healing period, and measurement (reference line and measurement level). Concerns over such heterogeneity were also stated well in recent systematic reviews (Avila‐Ortiz et al, ; Bassir et al, ; Troiano et al, ).…”
Section: Discussionsupporting
confidence: 62%
“…Several studies, including the present study, have demonstrated the effect of ARP specifically in molar areas (Cha et al, ; Lombardi et al, ; Walker et al, ; Zhao, Xu, Hu, & Chung, ). All of these studies favoured ARP over natural healing in terms of maintaining ridge dimension, but high heterogeneity among studies should be considered (Cha et al, ; Lombardi et al, ; Walker et al, ; Zhao et al, ), such as jaw and socket morphology, biomaterial, surgical technique (flap reflection and primary flap closure), healing period, and measurement (reference line and measurement level). Concerns over such heterogeneity were also stated well in recent systematic reviews (Avila‐Ortiz et al, ; Bassir et al, ; Troiano et al, ).…”
Section: Discussionsupporting
confidence: 62%
“…Seventy‐eight of these articles were excluded after full‐text review, the reasons for which are summarized in Table . Thus, the final selection was comprised of 28 articles, of which 25 were RCTs (Aimetti et al, 2009; Araujo et al, 2015; Avila‐Ortiz et al, 2020; Barone et al, 2008, 2017; Canellas et al, 2020; Cha et al, 2019; Clementini et al, 2019; Festa et al, 2013; Fiorellini et al, 2005; Hauser et al, 2013; Iasella et al, 2003; Jung et al, 2013; Karaca et al, 2015; Lim et al, 2019; Machtei et al, 2019; Pang et al, 2016; Pelegrine et al, 2010; Qabbani et al, 2017; Rasperini et al, 2010; Sisti et al, 2012; Spinato et al, 2014; Sun et al, 2019; Thalmair et al, 2013; Thoma et al, 2020) and three were non‐RCTs (Jiang et al, 2017; Sbordone et al, 2017; Zhao et al, 2018). Kappa scores for inter‐examiner agreement for title and abstract review as well as full‐text review were 0.91 and 0.82, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the group of PC teeth, significantly greater values were observed for the RAUB in the areas analyzed (33.45 %) compared to teeth in the PH group (19.65 %) (Independent t test; p < 0.05). This result is related to the fact that periodontal disease also results in the destruction of existing bone support (Van Der Weijden et al, 2009;Anwandter et al;Zhao et al, 2018). In addition, during the extraction procedure, the detachment of the cribriform plate can occur in the most apical area due to the fact that the tooth is strongly attached to the alveolus through the fibers of the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%